Macrolide resistance in Mycoplasma genitalium from female sex workers in Belgium. (March 2018) - Coorevits, Liselotte; Traen, Ans; Bingé, Luk; Descheemaeker, Patrick; Boelens, Jerina; Reynders, Marijke; Padalko, Elizaveta
Highlights: First report on macrolide resistance-associated mutations in M. genitalium in FSW in Belgium. Second report on the occurrence of macrolide resistance in this specific population worldwide. M. genitalium was detected in 32/296 (10.8%) of participants. Macrolide-resistance associated mutations (A2058G and A2059G) were found in 6.5% of isolates. In contrast to other reports, the occurrence of macrolide resistance appears limited in this specific population. Abstract: Objectives: Mycoplasma genitalium is emerging as an aetiological agent of sexually transmitted infections (STIs). Although M. genitalium is commonly treated with azithromycin, macrolide resistance associated with point mutations in the 23S rRNA gene is emerging. Methods: In this study, the prevalence of M. genitalium and macrolide resistance in female sex workers (FSW) in Belgium was evaluated by a prospective study conducted between 2015 and 2016. Vaginal swabs were sampled from 303 FSW who underwent testing for M. genitalium along with standard STI screening. All samples positive for M. genitalium were subsequently tested for mutations associated with macrolide resistance. Results: M. genitalium was detected in 10.8% of participants and macrolide resistance-associated mutations (A2058G and A2059G) were found in 6.5% of isolates. Conclusions: M. genitalium is clearly present in FSW in Belgium. In contrast to other reports, for now the occurrence of macrolide resistance appears limited in this specific target population.